Compresión lectora en inglés mediante el uso de herramientas interactivas en la básica secundaria (2019)
The investigation has as main purpose to develop reading comprehension in English language through the use of interactive tools in secondary school students. It works under a quantitative, descriptive approach, quasi-experimental design. A sample of 32 students in 9th grade from the Institucion Educativa Villa Estadio in the municipality of Soledad, Atlántico was intentionally selected. The investigation begins with a test (pretest) applied to the students in order to know the levels of reading comprehension in English, then interactive activities are applied through several interactive tools of author Jclic, Hot Potatoes and activities proposed by the virtual book, English please! 1 Fast Track Edition: Interactive Book - Grade 9, these are applied during an academic semester and, finally, a posttest is applied to assess the level of reading comprehension in English language. The results show that the students improved by 25,5% with respect to the level they initially had. It is concluded that the use of interactive tools in secondary school students at the Institucion Educativa Villa Estadio develops reading comprehension in English, especially at the level of literal reading comprehension.